Determinants of the social and economic development of Żórawina commune. Selected aspects - Wawrzynów, Piotr (Determinanty rozwoju społeczno-gospodarczego gminy Żórawina. Wybrane aspekty, 2018)
In today’s global economy, the local level is an important recipient of the effects of the processes and changes taking place. The goal of the article is to define the basic determinants of the social and economic development of Żórawina commune located in the region of Wrocław. In the first part of the article, the author points to the numerous different approaches to defining social and economic development; they also focus on the understanding of development at local level and determine the conditions constituting the basis for development. Then the general characteristics of the analysed commune are presented. The authors focused their considerations on selected conditions of the social and economic development of the studied area in order to create a detailed analysis of this space in the indicated scope. In the study, research conducted on the basis of literature and documents as well as simple statistical and descriptive methods were used
Biblioteka Regionalisty, 2018, Nr 18, s. 50-61
Keywords: commune; development factors; local development; gmina; czynniki rozwoju; rozwój lokalny